LAW ENFORCEMENT PROBLEMS AGAINST DRUG USERS (Study Decision Number: 214/Pid.Sus/2024/PN.Mdn) - Roslina Tiur Melia; Mhd. Azhali Siregar (International Journal of Society and Law, 2025)
Narcotics circulation and abuse is one of the national problems that are taken seriously by the government, because it can cause damage to the nation's morale, perpetrators of narcotics crimes often get punishment based on court decisions that lack a sense of justice and legal certainty. In narcotics cases, there are several articles that are often used to ensnare perpetrators, namely Article 114, Article 112, and Article 127 of Law Number 35 of 2009 concerning Narcotics. The three articles, there are two articles that have multiple interpretations and unclear formulations, namely in Article 112 and Article 127 of Law Number 35 of 2009 concerning Narcotics. The multi-interpretation article will result in narcotics crime perpetrators (dealers) taking refuge as if they were victims of narcotics crimes. That this will have an impact on the imposition of punishment with a short sentence so that it causes injustice in the implementation process. This research is normative juridical, which is a method that describes or explains a fact systematically and then the analysis is carried out juridically by linking the data and facts obtained by analyzing court decisions related to criminal sanctions against perpetrators of narcotics crimes and related to applicable laws and regulations. The results of this study However, in the field of narcotics law enforcement, this seems to be much more difficult. Prioritizing criminal punishment seems to be very inherent in our law enforcement body. It takes extraordinary encouragement both at the local, national and international levels. Therefore, in relation to the case in this study, the Judge of the Medan District Court decided that the defendant was legally and convincingly guilty in accordance with the provisions of article 112 paragraph (1) of UURI No.35 of 2009 concerning Narcotics by imposing a criminal sentence on the defendant Veri Suriana als Veri, therefore with a prison sentence for 6 (six) years and a fine of Rp.1,000,000,000,- (one billion rupiah) with the provision that if the fine is not paid, it must be replaced with imprisonment for 6 (six) months.